Pomegranate growing in Turkey - Ozgüven A.I.; Yilmaz C. (Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology, 2000)
Turkey is one of the native lands of the pomegranate, which has spread and is grown in every area, both in the coastal and the mountainous areas, up to altitudes of 1000 m. Pomegranate is mainly grown in the Aegean, Mediterranean and Southeastern Anatolia regions. Its cultivation has been increasing in Southern Anatolia region with a GAP project in recent years. Total pomegranate production in 1996 reached approximately 56,000 tons in Turkey, and the country is one of the world's important pomegranate export countries. There are different types and forms, because Turkey extends over large native areas of the pomegranate. In this respect, many selections are found which are the result of several breeding works. Selections have been examined under the Aegean, Mediterranean and Southern Anatolia ecological conditions, and their characteristics have been determined. Among the varieties represented, with respect to fruit taste, there are sour, sour-sweet and sweet varieties.
Symposium on 'Production, processing and marketing of pomegranate in the Mediterranean region: Advances in research and technology', 1998/10/15-17, Orihuela (Spain)